PERAN KEPALA SEKOLAH DALAM PENGEMBANGAN KEGIATAN EKSTRAKURIKULER KEPRAMUKAAN DI SEKOLAH MENENGAH ATAS AN-NUR II BULULAWANG MALANG - Nofi Rohmawati; Chalimatus Sa’dijah; Ika Anggraheni (VICRATINA, 2020)
The headmaster of An-Nur II Bululawang High School in Malang can encourage schools to realize their vision, mission, goals, through programs that are implemented, the scouting extracurricular development helps develop students in An-Nur II High School. Extracurricular good relationship with student achievement, An-Nur II high school students after following the scouting extracurricular have a positive impact when in the classroom the students are more active and skilled. to describe the implementation of the development of scouting extracurricular activities at An-Nur II Bululawang High School Malang. Qualitative research approaches andhcase study research types.Datakcollectionltechniques observation methods, interviews, documentation methods, the data presentation researchers used data reduction, data presentation, draw conclusions. Test the validity of the data by extending participation, perseverance of observation, triangulation, reference material. the principal's research findings have a Scouting program namely the Implementation of the Scouting Regular Regulatory System, through the areas of Routine Training, Facilities and Administration, finance and adult education activities. SKU Achievement Achievement of SKK, gives the opportunity to target scout coaches in 3 years. Scouting extracurricular activities are carried out on Saturdays at 5-8. Scouting was also held on Friday starting at 09.00-10.00 WIB.